Laser-Assisted Desorption/Ionization Mass Spectrometry Using Nanoporous SiO2 Aerogels for the Diagnosis of Colon Cancer - Yun, Tae Gyeong; Kim, Moon-Ju; Noh, Joo-Yoon; Song, Zhiquan; Kim, Younghun; Kang, Min-Jung; Park, Hyung-Ho; Pyun, Jae-Chul (American Chemical Society, 2022)
The SiO2 aerogel has a porous network of spherical silica particles with an average size of 3-5 nm, which provides an extremely high surface area. Herein, SiO2 aerogel was synthesized using the sol-gel method with sodium silicate as a precursor, and the SiO2 aerogel was applied to matrix-assisted laser desorption/ ionization mass spectrometry (MALDI-MS) as an inorganic matrix for quantitative analysis. In this work, a combi-matrix was prepared by mixing the SiO2 aerogel and a conventional organic matrix (CHCA) for quantitative analysis of analytes at an m/z ratio of less than 500. Using the combi-matrix based on the SiO2 aerogel with an extremely high porosity, analyte ionization was performed without the mass peaks of the organic matrix (CHCA) for MALDI-MS. The optimal ratio between the SiO2 aerogel and the organic matrix was determined to eliminate the mass peaks from the organic matrix and maximize the signal-to-noise ratio (S/N ratio) of the analytes. Quantitative analysis was performed using the optimal combi-matrix system (a mixture of SiO2 aerogel and organic matrix (CHCA)). The homogeneous and dense distribution of analytes was demonstrated using fluorescence imaging, and the spot-to-spot and shot-to-shot reproducibility was estimated using the SiO2 aerogel. Finally, LDI-MS based on the combi-matrix was applied for the quantitative analysis of a biomarker for colon cancer, dodecanoyl-L-carnitine (DC). Using real samples from healthy volunteers and patients, a medical diagnosis of colon cancer was demonstrated using a combi-matrix.